2007
DOI: 10.1002/asi.20709
|View full text |Cite
|
Sign up to set email alerts
|

Novelty and topicality in interactive information retrieval

Abstract: The information science research community is characterized by a paradigm split, with a system-centered cluster working on information retrieval (IR) algorithms and a user-centered cluster working on user behavior. The two clusters rarely leverage each other's insight and strength. One major suggestion from user-centered studies is to treat the relevance judgment of documents as a subjective, multidimensional, and dynamic concept rather than treating it as objective and based on topicality only. This study exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 31 publications
1
37
0
4
Order By: Relevance
“…There have been numerous attempts (Tombros, Ruthven, & Jose, 2005;Xu & Yin, 2008;Xu & Chen, 2006;Zhang, Zhang, Lease, & Gwizdka, 2014) to understand users' search behaviors when retrieving information with search engines, foe example, relevance judgment, satisfaction or dissatisfaction with search results. Understanding how users conduct relevance judgment and what factors influence users' satisfaction with the search results would help researchers design more effective retrieval models and better evaluation methodologies, aiming to further improve users' search experience.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been numerous attempts (Tombros, Ruthven, & Jose, 2005;Xu & Yin, 2008;Xu & Chen, 2006;Zhang, Zhang, Lease, & Gwizdka, 2014) to understand users' search behaviors when retrieving information with search engines, foe example, relevance judgment, satisfaction or dissatisfaction with search results. Understanding how users conduct relevance judgment and what factors influence users' satisfaction with the search results would help researchers design more effective retrieval models and better evaluation methodologies, aiming to further improve users' search experience.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies (Barry, 1998;Tombros et al, 2005;Xu & Yin, 2008;Xu & Chen, 2006;Zhang et al, 2014) have revealed that there exist a range of complex factors (e.g., topicality, novelty, reliability, understandability, and scope) affecting users' perception of relevance for the retrieved documents. However, the existing work is mainly based on small scale user studies, which may not reflect users' natural search scenarios, and the relevance judgments involved were made in a static way that cannot capture the dynamics of a user's information need, search interest, and habit.…”
Section: Introductionmentioning
confidence: 99%
“…Es importante plantear los principales criterios documentales en función del tipo de proceso comunicativo (argumentativo, narrativo, explicativo, instruccional, informe o informativo, etc.). En general, los criterios más importantes que deben regir la búsqueda de la información en un ámbito temático son la novedad (novelty) (Kumaran y Maguire, 2009) y la relevancia (Xu y Yin, 2008). Otros criterios son la accesibilidad de la información, la magnitud o nivel de afectación física, social, geográfica, económica, cultural… de la información, la jerarquía de los elementos informativos y la proximidad (geográfica y simbólica) del hecho informativo.…”
Section: Competencias Documentales Profesionalesunclassified
“…However, they do not take the quality of diversification into consideration. Several metrics, including the k-call metric [20] and a-NDCG [21], have been proposed for evaluating the diversity of search results. However, these metrics do not consider the relative importance of different categories (DCs) and how well a result matches a category.…”
Section: Dataset and Performance Measuresmentioning
confidence: 99%